2005
DOI: 10.1634/stemcells.2005-0204
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Cell Conditioned Medium Supports Differentiation of Embryonic Stem Cells into Ovarian Structures Containing Oocytes

Abstract: Previous reports and the current study have found that germ cell precursor cells appear in embryoid bodies (EBs) formed from mouse embryonic stem cells as identified by positive expression of specific germ cell markers such as Oct-3/4, Mvh, c-kit, Stella, and DAZL. We hypothesized that if exposed to appropriate growth factors, the germ cell precursor cells within the EBs would differentiate into gametes. The source for growth factors used in the present study is conditioned medium collected from testicular cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(179 citation statements)
references
References 55 publications
10
164
3
2
Order By: Relevance
“…In addition, eGFP-positive cell viability was increased since less degeneration was seen by day 2 in the EB culture when compared to the ES cells differentiated in monolayer. Several other investigators have demonstrated the ability of EBs to give rise to germ cells (both male and female) in culture [4,10,41,42]. This suggests that the three-dimensional structure of the EB may preserve greater intercellular communication between the cells, allowing for activation f the transcriptional machinery for oocyte-specific genes [43].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition, eGFP-positive cell viability was increased since less degeneration was seen by day 2 in the EB culture when compared to the ES cells differentiated in monolayer. Several other investigators have demonstrated the ability of EBs to give rise to germ cells (both male and female) in culture [4,10,41,42]. This suggests that the three-dimensional structure of the EB may preserve greater intercellular communication between the cells, allowing for activation f the transcriptional machinery for oocyte-specific genes [43].…”
Section: Discussionmentioning
confidence: 95%
“…When the transfected ES cells were allowed to form embryoid bodies (EBs) in culture [4,10], the appearance of eGFP-positive cells was again seen by d1. The eGFP-positive cells were seen clustered around the EBs and their structure was similar to that of the eGFP-positive cells that formed during in vitro differentiation of ES cells (Fig 5A).…”
Section: Gdf9 Promoter Function In Embryoid Bodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[5, 7,13,16,19,22,24,25,27] Cellules Sertoli, cellules Leydig, cellules de la granulosa, cellules de la thèque…”
Section: V-kit Hardy-zuckerman 4 Feline Sarcoma Viral Oncogene Homologunclassified